2016
DOI: 10.1091/mbc.e16-03-0205
|View full text |Cite
|
Sign up to set email alerts
|

The Ccz1-Mon1-Rab7 module and Rab5 control distinct steps of autophagy

Abstract: The endocytic Rab5 effectors Ccz1-Mon1 complex and Rab7 promote autophagosome-lysosome fusion independent of Rab5, which facilitates a later step of autophagy: degradation of cargo within lysosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
191
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(214 citation statements)
references
References 55 publications
13
191
0
10
Order By: Relevance
“…Confirming these results, TEM myofiber transverse sections (Figure 2B) revealed Rab2 , Rab7 or Stx17 RNAi-depleted IOMs similarly and uniformly filled with thousands of accumulated autophagosomes carrying nondegraded cytoplasm and organelles (Figure 4E–F). Thus, similar to previous reports of Rab7, Stx17, SNAP29 and Vamp7/8 functions in other Drosophila tissues (Hegedűs et al, 2016; Takáts et al, 2013), with myofiber remodeling, Rab2 also is required for autophagosome-lysosome fusion.
10.7554/eLife.23367.009Figure 4.Autophagosomes accumulate in IOMs with Rab2, Rab7 or Stx17 knockdown.All IOMs imaged at 4d APF. ( A ) Autophagic flux assay using tandem-tagged mCherry:GFP:Atg8 (mCherry (C), pink; GFP (G), green; colocalization, white).
…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Confirming these results, TEM myofiber transverse sections (Figure 2B) revealed Rab2 , Rab7 or Stx17 RNAi-depleted IOMs similarly and uniformly filled with thousands of accumulated autophagosomes carrying nondegraded cytoplasm and organelles (Figure 4E–F). Thus, similar to previous reports of Rab7, Stx17, SNAP29 and Vamp7/8 functions in other Drosophila tissues (Hegedűs et al, 2016; Takáts et al, 2013), with myofiber remodeling, Rab2 also is required for autophagosome-lysosome fusion.
10.7554/eLife.23367.009Figure 4.Autophagosomes accumulate in IOMs with Rab2, Rab7 or Stx17 knockdown.All IOMs imaged at 4d APF. ( A ) Autophagic flux assay using tandem-tagged mCherry:GFP:Atg8 (mCherry (C), pink; GFP (G), green; colocalization, white).
…”
Section: Resultssupporting
confidence: 85%
“…Indeed, it has been shown that four of the five genes play known roles together in lysosome fusion: Stx17, SNAP29, and Vamp7/8 form a trans-SNARE complex involved in autophagosome-lysosome fusion (Itakura et al, 2012; Takáts et al, 2013), while Rab7 functions in late endosome-lysosome fusion as well as late steps in autophagy (Gutierrez et al, 2004; Jäger et al, 2004; Hegedűs et al, 2016). It was unexpected, however, to find a shared RNAi phenotype between this set of known functions and Rab2, which had been implicated with functions at the ER and Golgi (Saraste, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 , 42 , 4648 Indeed, by first using a HeLa model cell system, we demonstrate that, different from the wild-type protein, these mutants fail to increase the number of autophagosomes both in basal conditions and after stimulation, behaving similarly to the dominant negative and functionally impaired RAB7 T22N mutant. Still, while model cell lines are widely used as easily manageable tools to understand molecular mechanisms involved in a wide variety of cellular phenomena, they do not necessarily fully recapitulate the biological conditions of affected cells in vivo.…”
Section: Discussionmentioning
confidence: 83%
“…We therefore tested if autophagy is also differentially regulated by the nutrient level in C4da neurons and epidermal cells. To examine the autophagy level, we used an mCherry-Atg8a reporter under the control of the endogenous Atg8a regulatory sequence, which labels autophagic structures (Hegedus et al, 2016). As expected, the autophagosome level in epidermal cells was low under the HY condition (Figure 3A) but increased 5 folds in the LY diet (Figures 3B and 3C).…”
Section: Resultsmentioning
confidence: 99%